Standar Kompetensi Aparatur Pemerintah; Urgensi, Model Dan Proses Penyusunannya - Amalia, Shafiera (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2011)
Nowadays, quality human resource becomes capital of an organization, which influences performance. Both public and private organizations need competency based human resources management to gain and maintain competent employees. Competency standard is essential for assessing employee’s competency. Therefore, in order to implement competency based human resources management, competency standard is the very first thing to create and it must be used in human resources management processes, like recruitment, placement promotion and development. Some model are used to create Competency Standard, but Indonesian Human Resourches Management has not already decided the model to create competency standard. It causes the model of competency standard one of government organization may different with another organization. Thus, the model of competency standard have to be decided as a guideline to create competency standard for Indonesian Government Apparatus. This way, quality human resources will be gained and maintained, and eventually they will help organization increase its performance.